Complications of Hip Arthroscopy: Patient Perspectives. (July 2016) - Sharfman, Zachary T.; Amar, Eyal; Tsvieli, Oren; Alkrinawi, Nassim; Levy, Ofer; Rath, Ehud
Abstract : BACKGROUND: In recent years, hip arthroscopy has rapidly evolved, offering patients evidence-based interventions with the merits of minimally invasive surgery and a relatively short rehabilitation period. Although considered a safe procedure, hip arthroscopy has associated complications that may be underreported depending on how patients are asked about their complications. PURPOSE: The aim of this study was to evaluate hip arthroscopy complications from the patient's perspective. METHODS: Between February 2006 and April 2010, a total of 78 consecutive patients underwent arthroscopy of the hip by a single surgeon. A questionnaire was created that included questions regarding demographic data, functional data, and the patient's opinion as to the operation's indications, subjective evaluation of the success of the procedure, and the presence of specific complications. Patients were asked about the presence of specific complications rather than being asked about the presence of any complication in general. RESULTS: Sixty-two patients participated. The mean time postsurgery was 27.9 months (range = 5–55 months). Main indications for surgery were correction of femoroacetabular impingement in 31 (50%) patients. Mean surgery time was 1.2 hours (range = 0.5–2.43 hours), mean postoperative modified Harris hip score (MHHS) was 76.2 (range = 15–100), and mean postoperative pain score was 4 (range = 2–10). Fifteen (24%) patients reported complications after surgery, with 20 complications reported overall (32%). Eight (12.9%) patients reported transient neuropraxias. No significant differences were found between patients reporting complications and patients not reporting complications in terms of age, gender distribution, surgery time, visual analog scale score, MHHS, and time from surgery. CONCLUSIONS: When patients are asked a general question, whether they suffer from any complications, they tend to underreport the presence of such complications. Complete and comprehensive interviews of the patient may give us a better understanding of the true incidence of complications.